2022
DOI: 10.3389/fmicb.2022.841529
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community and Metabolite Dynamics During Soy Sauce Koji Making

Abstract: Koji making is a pre-fermentation stage in soy sauce manufacturing that impacts final product quality. Previous studies have provided valuable insights into the microbial species present in koji. However, changes in microbial community functional potential during koji-making are not well-known, nor are the associations among microbial populations and flavoring characteristics. In the present study, we investigated the succession of microbial communities, microbial community functional potential, metabolite pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…After 1 month of fermentation, an aging process will occur, which causes the color change in the soy sauce to become darker and gives rise to a distinctive aroma. The aging process is dominated by the role of Bacillus via amylase and protease activities [19]. Moreover, the longer the fermentation process, the darker the color of the soy sauce due to the formation of melanoidin's resulting from the amino-carbonyl reaction ween amino compounds and reducing sugars during the fermentation process [20].…”
Section: Resultsmentioning
confidence: 99%
“…After 1 month of fermentation, an aging process will occur, which causes the color change in the soy sauce to become darker and gives rise to a distinctive aroma. The aging process is dominated by the role of Bacillus via amylase and protease activities [19]. Moreover, the longer the fermentation process, the darker the color of the soy sauce due to the formation of melanoidin's resulting from the amino-carbonyl reaction ween amino compounds and reducing sugars during the fermentation process [20].…”
Section: Resultsmentioning
confidence: 99%
“…Staphylococcus, Bacillus, Weissella, Aspergillus , and Zygosaccharomyces were closely related to the formation of the flavor of BBP because of their abundance and their involvement in the flavor biosynthesis during fermentation (Jia et al, 2021 ). Tan et al ( 2022 ) reported that the abundances of Aspergillus, Kocuria, Enterococcus, Lactococcus , and Corynebacterium were all positively correlated with the concentrations of all amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…In Hainan tobacco leaves, Kocuria showed a positive correlation with 2-acetylfuran, isophorone, 2, 6-nonadienal, and β-damascenone. Similarly, Kocuria has been reported to be the functional microbe responsible for the production of amino acids and flavor compounds (i.e., phenylethanol, acetic acid) in many fermented foods, such as Suanyu, cheese, and soy sauce (Centeno et al 2017 ; Tan et al 2022 ; Zang et al 2022 ). Staphylococcus displayed a low correlation coefficient with aromatic substances, potentially indicating that it is not directly involved in the synthesis and metabolism of aromatic substances.…”
Section: Resultsmentioning
confidence: 99%